Shuttle walking test in obese women: test‐retest reliability and concurrent validity with peak oxygen uptake. (3rd March 2014) - Jürgensen, Soraia P.; Trimer, Renata; Dourado, Victor Z.; Di Thommazo‐Luporini, Luciana; Bonjorno‐Junior, José C.; Oliveira, Cláudio R.; Arena, Ross; Mendes, Renata G.; Borghi‐Silva, Audrey
Summary Objective The aim of this study was to evaluate the test–retest reliability, concurrent validity and agreement with peak oxygen uptake (VO2) obtained during cardiopulmonary exercise testing (CPX) on a treadmill for the incremental shuttle walking test (ISWT) in obese women. Methods Prospective study with a convenient sample of 46 community‐dwelling obese women (BMI > 30 kg m−2). The main outcome measures were walking distance on the ISWT and peak VO2. Results Test–retest reliability was good to excellent for the exercise tests (ISWT distance ICC: 0·90; and CPX peak VO2 ICC: 0·90). Peak VO2 obtained during CPX correlated significantly with ISWT distance (r = 0·54, P<0·05) and peak VO2 obtained during the ISWT (r = 0·64, P<0·05). Bland and Altman plots demonstrated a high degree of repeatability. Conclusion The ISWT had excellent reliability as well as good concurrent validity and agreement. The ISWT may be a potential tool for monitoring clinical status and intervention efficacy (e.g. programmes for weight loss and rehabilitative strategies) in this population.